OsVIT2 Mutation Increases Fe and Zn of Grain Without Compromising the Growth in Paddy Field - Kandwal, Prashant; Fujiwara, Toru; Kamiya, Takehiro (Frontiers in Plant Science, 2022)
Nearly 2 billion people who reside in developing countries are suffering from nutrient deficiency, called hidden hunger. Iron (Fe) and zinc (Zn) deficiency are among the major hidden hunger. One of the solutions for hidden hunger is the biofortification of crops by breeding. In this study, we characterized the mutant 1095_k, which has high grain Fe (~1.4 fold) and Zn (~1.2 fold) concentration compared with wild-type grains for a five-year field trial. The yield components of 1095_k is similar to wild-type plants in a paddy field. 1095_k has a non-sense mutation in OsVIT2, a vacuolar localized Fe transporter. F2 crosses between 1095_k and wild type having the mutation showed higher grain Fe and Zn concentration. In contrast, plants without the mutation showed similar elements concentrations as wild type. These results suggest that OsVIT2 would be responsible for high Fe and Zn of grain and the 1095_k would be a useful breeding material for the biofortification of Fe and Zn.